Use of Carrier Ampholyte-Free Isoelectric Focusing for Proteomic Analysis - PROCHAZKOVA, Barbora; SALPLACHTA, Jirri (Chromatographia, 2008)
Carrier ampholyte-free isoelectric focusing was applied for pre-concentration, purification and micropreparation of phycobiliproteins (C-phycocyanin, allophycocyanin, B-phycoerythrin) extracted from cyanobacteria Anabeana doliolum and from red microalga Porphyridium cruentum. The extraction of phycobiliproteins was carried out in deionized water. The sonication in the ultrasonic bath and liquid nitrogen freeze grind was used for extraction of proteins of interest. Pre-concentrated and pre-separated proteins were collected and analyzed via MALDI-TOF-TOF mass spectrometer after their proteolytic digestion via trypsin. Based on tandem mass spectrometric analysis, the C-phycocyanin, allophycocyanin and B-phycoerythrin were identified unambiguously.